THE EVOLUTION OF ARCHETYPAL STRUCTURE IN ADYGHE HISTORICAL-HEROIC EPIC - A. М. GUTOV (Кавказология, 2019)
The article deals with the problem of the evolution of the archetypal structure, which passed from myth to archaic epic and preserved due to the ability to adapt to changes in socio-cultural and ideological character. Based on the plots of historical and heroic tales that arose at a relatively late stage of the productive life of the folk epic, the main stages of the evolution of the motive of the miraculous birth of the hero are investigated. Attention is drawn to the progressive changes in public consciousness, which caused the transition of mythological narrative in the field of artistic creativity, then analyzes the various forms of implementation of the archaic model of the narrative, directly in connection with the stadium changes in the perception of the world and the nature of the reflection of reality in the genres of folklore. It is established that both the motive in question and some others, which originated as methods of intergenerational transmission of beliefs, must have been originally included in the ritual of an initial character. The secularization of the mythological narrative does not separate the motive from the original system of perception of the world. Therefore, in the early type of epic, the motif may remain in form extremely close to the myth. But it still enhances the aesthetic function of the narrative, so that in the later epic cycles, the initial structure acquires a new design, in accordance with the evolutionary processes in the field of perception.